The Influence of Product Design, Price Perception, Location, and Advertising on the Purchasing Decision of Green Teksin Houses at PT. Asset Management Company (PPA) Tegal Regency - Poppy Kusuma Buana Rahajeng PUTRI; Tabrani TABRANI; Yuniarti HERWINARNI (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2025)
The purpose of this study is to determine whether there is an influence of product design (X1) on purchasing decisions (Y), the influence of price perception (X2) on purchasing decisions (Y), the influence of location (X3) on purchasing decisions (Y), the influence of advertising (X4) on purchasing decisions (Y) and to determine how much product design (X1), price perception (X2), location (X3) and advertising (X4) together on purchasing decisions (Y). The method used in this study is a survey method with a quantitative approach through multiple linear regression analysis. The number of samples is 100 respondents who are consumers who have purchased a house in the Green Teksin housing complex in Tegal Regency. The results show that the product design variable (X1) has a positive and significant effect on purchasing decisions. The price perception variable (X2) has a positive and significant effect on purchasing decisions. The location variable (X3) has a positive and significant effect on purchasing decisions. At the same time, the advertising variable (X4) has a positive and significant effect on purchasing decisions. Simultaneously, it shows that the four independent variables have a significant effect on purchasing decisions for Green Teksin houses at PT. Asset Management Company (PPA) in Tegal Regency.